1968
DOI: 10.1001/jama.1968.03140030033008
|View full text |Cite
|
Sign up to set email alerts
|

A Means of Assessing Maximal Oxygen Intake

Abstract: One hundred and fifteen US Air Force male officers and airmen were evaluated on a 12-minute field performance test and on a treadmill maximal-oxygen-consumption test. The correlation of the field-test data with the l aboratory\x=req-\ determined oxygen-consumption data was 0.897. The significance of this relationship makes it possible to estimate with considerable accuracy the maximal oxygen consumption from only the results of the 12-minute performance test. This test is readily adaptable to large groups, req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
235
0
31

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 694 publications
(293 citation statements)
references
References 2 publications
5
235
0
31
Order By: Relevance
“…18 To study the aerobic capacity, the participants performed the Cooper test 18 and the estimated VO 2max values (R = 0.90) were calculated using the Cooper test equation [VO 2max = 22.351 × (distance; in m)/1000) − 11.288]. 20 To perform the Back-Saver Sitand-Reach test, the participants completed three trials on a flex tester (AcuFlex, Novel Products Inc, Addison, IL, USA), as reported by the Cooper Institute for Aerobics Research. 21 The best score was recorded for analysis (in cm).…”
Section: Physiological Profilingmentioning
confidence: 99%
“…18 To study the aerobic capacity, the participants performed the Cooper test 18 and the estimated VO 2max values (R = 0.90) were calculated using the Cooper test equation [VO 2max = 22.351 × (distance; in m)/1000) − 11.288]. 20 To perform the Back-Saver Sitand-Reach test, the participants completed three trials on a flex tester (AcuFlex, Novel Products Inc, Addison, IL, USA), as reported by the Cooper Institute for Aerobics Research. 21 The best score was recorded for analysis (in cm).…”
Section: Physiological Profilingmentioning
confidence: 99%
“…Skin fold thickness was measured by skin fold calliper at subscapular region, supra-iliac region and abdomen, after that sum of the skin folds was calculated which reflects absolute or percentage changes in body fat [21]. VO 2 max (ml/kg/min) was measured using " Cooper 12 Minute Walk test", total distance was recorded in meters they had travelled in 12 minutes then it converted in kilometre and put it in the formula: VO2 max = (22.351 x kilometres) -11.288 [22,23]. In order to determine health related quality of life RAND 36 -Item health survey 1.0 scales was used.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is known that protocols for VO 2max measurement, for example, require trained professionals, special equipment and need to be conducted in a controlled environment. The first field test used to measure vVO 2max was intended to replace the 12 min test Cooper (Cooper 1968) as an alternative to predict VO 2max in a unique effort to simplify procedures and reduce costs. Cooper (1968) reported a correlation of 0.9 between VO 2max and the distance covered in a 12 min test running or walking.…”
Section: Velocity At Vo 2max (Vvo 2max )mentioning
confidence: 99%
“…The first field test used to measure vVO 2max was intended to replace the 12 min test Cooper (Cooper 1968) as an alternative to predict VO 2max in a unique effort to simplify procedures and reduce costs. Cooper (1968) reported a correlation of 0.9 between VO 2max and the distance covered in a 12 min test running or walking. However, the motivation and rhythm was mentioned as critical to achieve good reliability in a 12 min test (Cooper 1968).…”
Section: Velocity At Vo 2max (Vvo 2max )mentioning
confidence: 99%